Temperature Dependence of Rate Processes Beyond Arrhenius and Eyring: Activation and Transitivity - Carvalho-Silva, Valter H.; Coutinho, Nayara D.; Aquilanti, Vincenzo (Frontiers in Chemistry, 2019)
Advances in understanding in the dependence of reaction rates from temperature, as motivated from progress in experiments and theoretical tools (e.g. molecular dynamics), are needed for the modeling of extreme environmental conditions (e.g. in astrochemistry and in the chemistry of plasmas). While investigating statistical mechanics perspectives (Aquilanti et al., 2017b, 2018), the concept of transitivity was introduced as a measure for the propensity for a reaction to occur. The Transitivity plot is here defined as the reciprocal of the apparent activation energy vs reciprocal absolute temperature. Since the transitivity function regulates transit in physicochemical transformations, not necessarily involving reference to transition-state hypothesis of Eyring, an extended version is here proposed to cope with general types of transformations. The transitivity plot permits a representation where deviations from Arrhenius behavior are given a geometrical meaning and make explicit a positive or negative linear dependence of transitivity for sub- and super-Arrhenius cases, respectively. To first-order in reciprocal temperature, the transitivity function models deviations from linearity in Arrhenius plots as originally proposed by Aquilanti and Mundim: when deviations are increasingly larger, other phenomenological formulas, such as Vogel-Fulcher-Tamman, Nakamura-Takayanagi-Sato and Aquilanti-Sanches-Coutinho-Carvalho are here rediscussed from the transitivity concept perspective and with a general context. Emphasized is the interest of introducing into this context modifications to a very successful tool of theoretical kinetics, Eyring’s Transition-State Theory: considering the behavior of the transitivity function at low temperatures, in order to describe deviation from Arrhenius behavior under quantum tunneling regime, a ‘d-TST’ formulation was previously introduced (Carvalho-Silva et al., 2017). In this paper, a special attention is dedicated to a derivation of the temperature dependence of viscosity, making explicit reference to feature of the transitivity function, which in this case generally exhibits a super-Arrhenius behavior. This is of relevance also for advantages of using the transitivity function for diffusion-controlled phenomena.